Contemporary Fairy Tales. Themes, values, narratological perspectives in the time of pandemic - Boero, Marianna (Opción, 2022)
This work aims to reflect on the changes of fairy tales in contemporary society, both in terms of narrative methods, increasingly conditioned by the advent of social media, and the covered topics, increasingly complex and in line with the social changes, and the methodologies, oriented to an interdisciplinary dialogue. For this purpose, this paper identifies some of the main themes of contemporary Italian fairy tales and then extends the gaze to the fairy tale as a support and narrative tool in the era of Covid-19 pandemic.